Personalizable Information Interchange Architecture for EducationalInstitutions - Ting, Tin Tin; Khoo, Kay Teong (2008)
This paper proposes a personalizable service oriented architecture for the interchange of information between educational institutions through an intermediate party. The issues pertaining to standards-personalization convergence are first discussed, followed by a description of the proposed architecture, and an evaluation of its performance at three levels of granularity.